PENYULUHAN TATANEN DALAM MENINGKATKAN KOMPETENSI ABAD 21 MELALUI PROJECT BASED LEARNING BERBASIS STEM TDBA - Kurniasih Kurniasih; Dewi Kartika; Nevlida Lumban Gaol; Ihat Nur Hamidah; Siti Hindun Marhamah; Dini Nur Anggraeni; Sofyan Iskandar (Pusat Pengembangan dan Kajian Sarana dan Prasarana Pendidikan (P2K Sarprasdik), 2021)
Abstract: The service . The service carried out has the aim of providing insight and knowledge about how to do Tatanen Di Balé Atikan or farming in educational institutions. Tatanen Di Balé Atikan is currently being intensified in Purwakarta Regency. TDBA is defined as the act of teaching characteristics in increasing the importance of caring for the earth for awareness of how to live ecologically. The implementation of the Tatanen movement at Bale Atikan aims to shape student character through environmental preservation. The target of this service activity is the VE class students of SDN 1 Nagrikidul Purwakarta, totaling 30 students. The method used in the service is the method of lectures, discussions, questions and answers, and demonstrations which are carried out using a learning model that is suitable to facilitate the student learning process, namely the project based learning model. The service that was carried out invites students to take part in the Tatanen Di Balé Atikan activities based on Science, Technology, Engineering, and Mathematics (STEM) which include getting to know the process of making raised beds and cultivating soil as a good planting medium, by being invited to directly participate in these activities. . Introducing tools and materials for making beds and planting media to elementary school students can be done while playing and being creative with the aim of making it easier for students to receive and understand the information and knowledge gained in these activities. The enthusiasm shown by students in these activities is very high, this can be seen when students are very enthusiastic in participating in community service activities starting at the beginning of the activity until the end of the activity.Abstrak: Pengabdian yang dilakukan dengan menggunakan model pembelajaran yang cocok untuk memudahkan proses belajar siswa yaitu model pembelajaran berbasis proyek (project based learning). Pengabdian yang dilakukan tersebut mengajak siswa untuk mengikuti kegiatan Tatanen Di Balé Atikan berbasis Sains, Technology, Engineering, and Mathematics (STEM) yang diantaranya mengenal proses pembuatan bedengan dan pengolahan tanah sebagai media tanam yang baik, dengan cara siswa diajak terjun secara langsung dalam kegiatan tersebut. Mengenalkan alat dan bahan untuk membuat bedengan dan media tanam kepada siswa sekolah dasar dapat dilakukan sambil bermain dan berkreasi yang bertujuan supaya mempermudah siswa dalam menerima dan memahami informasi serta ilmu yang didapat dalam kegiatan tersebut. Antusiasme yang ditunjukkan oleh siswa dalam kegiatan tersebut sangatlah tinggi, hal tersebut dilihat ketika siswa sangat bersemangat dalam mengikuti kegiatan pengabdian mulai di awal kegiatan hingga berakhirnya kegiatan.